2007 IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications 2007
DOI: 10.1109/pimrc.2007.4394652
|View full text |Cite
|
Sign up to set email alerts
|

ICI-ISI Mitigation in Cooperative SFBC-OFDM with Carrier Frequency Offset

Abstract: Synchronization issues pose a big challenge in cooperative communications. The benefits of cooperative diversity could be easily undone by improper synchronization. The problem arises because it would be difficult, from a complexity perspective, for multiple transmitting nodes to synchronize to a single receiver. For OFDM based systems, loss of performance due to imperfect carrier synchronization is severe, since it results in inter-carrier interference (ICI). The use of space-time/spacefrequency codes from or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In the expression for the ICI at destination given by (16), the first term is caused by a CPE term at relay while the second and the third terms are due to the ICI at relay and AWGN enhanced by energy of a PN term. In the high SNR region, the first and the second terms in the above expression drastically increase causing further performance degradation due to the PN and consequently, limits the system's performance.…”
Section: Sinr Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the expression for the ICI at destination given by (16), the first term is caused by a CPE term at relay while the second and the third terms are due to the ICI at relay and AWGN enhanced by energy of a PN term. In the high SNR region, the first and the second terms in the above expression drastically increase causing further performance degradation due to the PN and consequently, limits the system's performance.…”
Section: Sinr Degradationmentioning
confidence: 99%
“…Implementation of ANC scheme in frequencydomain was presented in [15], and carrier frequency offset compensation is considered at relay to capture the effect of PN in ANC scheme. In [16], impact of ICI on cooperative SFBC-OFDM is theoretically analyzed and an iterative algorithm for inter-symbol interference (ISI) and ICI cancelation is proposed. It was showed that the two-step cancelation algorithm can efficiently suppress the ICI and ISI.…”
Section: Introductionmentioning
confidence: 99%
“…S,2 and η DF S are defined in (6). Unlike the AF mode, since the interference generated in the S → R transmission is eliminated in the DF mode, the effective Signal-to-Interference-plus-Noise Ratio (SINR) in the DF mode is improved considerably, but at the cost of an additional complexity in hardware design in each relay.…”
Section: B Df Modementioning
confidence: 99%
“…A hybrid forwarding scheme for cooperative relaying in Orthogonal Frequency-Division Multiplex (OFDM)-based networks without considering the frequency offset is proposed in [5]. Both the inter-symbol-interference (ISI) and the inter-carrier-interference (ICI) mitigation in a cooperative space-frequency block coded (SFBC) OFDM by considering the frequency offset is analyzed in [6]. A spacetime cooperative OFDM (CO-OFDM) system in the presence of the frequency offset is proposed in [7], where a diversity gain comparable to that of the conventional space-time coded OFDM system can be achieved in CO-OFDM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of frequency offset, which degrades the Signalto-Interference-plus-Noise Ratio (SINR), is not considered in [3]. The effect of the frequency offset on cooperative OFDM or OFDM access (OFDMA) uplink transmission is studied in [4], [5]. The performance degradation of a cooperative OFDMA uplink due to the frequency offset is analyzed in [6].…”
Section: Introductionmentioning
confidence: 99%